Knowledge, Attitude, Awareness, and Practice Regarding Demodex Mites Among the Thai Population - Paichitrojjana A; Paichitrojjana A (Patient Preference and Adherence)
Anon Paichitrojjana,1 Anand Paichitrojjana2 1School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Bangkok, Thailand; 2Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Anon Paichitrojjana, Email anonpaic@gmail.comBackground: Demodex mites are common ectoparasites in humans and can cause various skin disorders known as demodicosis, ranging from nonspecific facial dermatitis to conditions resembling eczema, seborrheic dermatitis, folliculitis, and acne. Overgrowth of these mites can lead to pityriasis folliculorum, perioral dermatitis, blepharitis, and rosacea, significantly impacting skin health. This study aims to investigate the knowledge, attitude, awareness, and practice regarding Demodex mites in the Thai population and analyze the influencing factors associated with these aspects.Methods: This study is a cross-sectional, analytical, observational study. All participants completed a questionnaire that covered sociodemographic characteristics, knowledge, attitude, awareness, practice regarding Demodex mites, and sources of health information. The survey was distributed via Google Forms, social media platforms, and paper questionnaires.Results: Among 540 participants, the average age was 38.65 years, with 52% males. Mean scores for knowledge, attitude, awareness, and practice were 4.56 ± 2.56 out of 10, 17.37 ± 3.88 out of 25, 13.52 ± 3.59 out of 25, and 18.57 ± 3.73 out of 25, respectively. Only 23.33% had adequate knowledge, 50.56% had positive attitudes, and 10.93% had sufficient awareness. However, 66.11% exhibited active practices. Factors associated with active practice included being female (AOR = 1.95, p = 0.003), adequate knowledge (AOR = 1.63, p = 0.042), positive attitudes (AOR = 1.83, p = 0.002), and sufficient awareness (AOR = 4.12, p = 0.001).Conclusion: The study clearly showed that the knowledge of Demodex mites among Thai people is limited. Although their attitudes toward these mites are fairy positive, their awareness remains alarmingly low. Nevertheless, they do engage in practices related to personal hygiene. Therefore, it is essential to improve this situation through effective educational campaigns to significantly enhance the management of skin diseases caused by Demodex mites.Keywords: knowledge, attitude, awareness, practice, Demodex mite